2021
DOI: 10.1093/jxb/erab216
|View full text |Cite
|
Sign up to set email alerts
|

Genetic autonomy and low singlet oxygen yield support kleptoplast functionality in photosynthetic sea slugs

Abstract: Elysia chlorotica is a kleptoplastic sea slug that preys on Vaucheria litorea, stealing its plastids which continue to photosynthesize for months inside the animal cells. We investigated the native properties of V. litorea plastids to understand how they withstand the rigors of photosynthesis in isolation. Transcription of specific genes in laboratory-isolated V. litorea plastids was monitored up to seven days. The involvement of plastid-encoded FtsH, a key plastid maintenance protease, in recovery from photoi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 71 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…The results of these two studies contradict each other, as Christa et al did not find any significant differences in the recovery of PSII in the presence or absence of lincomycin, whereas our data showed that lincomycin efficiently blocks the recovery process in photoinhibited plastids of E. timida. Our results would imply that freshly fed slugs do retain some capacity for PSII repair even without the help of the algal nucleus that encodes many of the proteins that are known to be related to the repair cycle at least in plants (Järvi et al 2015;Havurinne et al 2021). However, additional support for the existence of deficiencies in the PSII repair cycle in the slug plastids is available in the literature.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…The results of these two studies contradict each other, as Christa et al did not find any significant differences in the recovery of PSII in the presence or absence of lincomycin, whereas our data showed that lincomycin efficiently blocks the recovery process in photoinhibited plastids of E. timida. Our results would imply that freshly fed slugs do retain some capacity for PSII repair even without the help of the algal nucleus that encodes many of the proteins that are known to be related to the repair cycle at least in plants (Järvi et al 2015;Havurinne et al 2021). However, additional support for the existence of deficiencies in the PSII repair cycle in the slug plastids is available in the literature.…”
Section: Introductionmentioning
confidence: 85%
“…S1 in Online Resource). Effectiveness of 10 mg/ml lincomycin in stopping PSII repair cycle in the slug plastids has been illustrated previously (Havurinne et al 2021).…”
Section: Photoinhibition Treatmentsmentioning
confidence: 93%
See 3 more Smart Citations